Four new species of the genus Mongoliana Distant (Hemiptera: Fulgoromorpha: Issidae) from southern China - Meng, Rui; Wang, Yinglun; Qin, Daozheng (Zootaxa, 2016)
Four new species in the planthopper genus Mongoliana Distant from southern China (Hemiptera: Fulgoromorpha: Issidae) are reported. Three of them, M. bistriata sp. nov., M. latistriata sp. nov. and M. albimaculata sp. nov., are described and illustrated; the fourth new one, M. arcuata sp. nov., is briefly described for M. triangularis Chen, Zhang & Chang which was a misidentification of M. triangularis Che, Wang & Chou. M. recurrens (Butler, 1875) is re-described and remarks for its current status is given. A key to all known species of Mongoliana is provided. The distribution and morphological peculiarities of the genus are briefly discussed.